On the mechanism of photoinduced dimer dissociation in the plant UVR8 photoreceptor - Voityuk, Alexander A. (2014)
UV-B absorption by the photoreceptor UV resistance locus 8 (UVR8) consisting of two identical protein units triggers a signal chain used by plants in connection with protection and repair of UV-B induced damage. X-ray structural analysis of the purified protein [Christie JM, et al. (2012) Science 335(6075):1492–1496] [Wu D, et al. (2012) Nature 484(7393): 214–220] has revealed that the dimer is held together by arginine–aspartate salt bridges. In this paper we address the initial processes in the signal chain. On the basis of high-level quantum-chemical calculations, we propose a mechanism for the photodissociation of UVR8 that consists of three steps: (i) In each monomer, multiple tryptophans form an extended light-harvesting system in which the La excited state of Trp233 experiences strong electrostatic stabilization by the protein environment. The strong stabilization singles out this tryptophan to be an efficient exciton acceptor that accumulates the excitation energy from the entire protein subunit. (ii) A fast decay of the locally excited state by charge separation generates the radical ion pair Trp285(+)-Trp233(−) with a dipole moment of ∼18 D. (iii) Key to the proposed mechanism is that this large dipole moment drives the breaking of the salt bridges between the two monomer subunits. The suggested mechanism for the UV-B–driven dissociation of the dimer that rests on the prominent players Trp233 and Trp285 explains the experimental results obtained from mutagenesis of UVR8.